POTENSI WISATA ALAM GUNUNG ROBAN DI KELURAHAN PAJINTAN KECAMATAN SINGKAWANG TIMUR Pontential Nature Roban Mountain in Pajintan Village District East Singkawang - rizal, Fah; Roslinda, Emi; Ardian, Hafiz (Universitas Tanjungpura, 2014)
Roban mountain area become alternative natural tourist destination in Singkawang its natural beauty. However, until now there is no need of the local government and the private sector for the development of its tourism. Perhaps, due to the lack of information about the potential attractiveness of Roban Mountain area. The purpose of this study was to looking for data on the potential attractiveness of the region Roban Mountain area. Data processing done by descriptive analysis is performed a weighting and assessment based on the Guidelines for Regional Operations Analysis Objects and Attraction Nature Directorate General of PHKA (2003) which has been modified. The most popular attraction in Roban Mountain area : the view from the top of the mountain, integrity of natural resources, fres air and good atmosphere. Climbing activity is the most popular visitor activity. The assessment result all of attraction criteria have score 1233,42 that means this area have potential attraction (B). This value indicates Roban Mountain area could be developed into a tourist destination of nature. Keywords: Roban mountain, tourism potential, nature tourism, villa di puncak